The usefulness of Ramfjord teeth to represent the full-mouth pocket depth in epidemiological study (Mustansiria Dental Journal, 2018)
Partial recording of indices of periodontitis have long been used in clinical andepidemiological studies to predict full-mouth situation. The two most widely usedpartial recording indices for periodontal surveys are the community periodontal indexof treatment needs (CPITN) and the Ramfjord teeth.The aim of this study was to evaluate the usefulness of Ramfjord teeth inpredicting the full-mouth periodontal status of an adult population in patient attendingthe collage of dentistry- Baghdad University.The study participants were 240 patients we divide them into three main groupsaccording to the age of the patients and each group were divided in to two sub groupsaccording to the sex of the patients. Pocket depth was measured in millimeters withperiodontal probeThe difference in the mean pocket depth measured from the full mouth(F) andRamfjord teeth(R) by using paired t - test was non significant in all the groups. Alsoin all groups the correlation coefficient as well as beta coefficient was highThe high agreement between Ramfjord teeth and full mouth periodontal pocketdepth confirm the epidemiological validity of Ramfjord teeth to represent the fullmouth.